2016
DOI: 10.1111/jac.12181
|View full text |Cite
|
Sign up to set email alerts
|

Improved Salinity Tolerance by Phosphorus Fertilizer in Two Phaseolus vulgaris Recombinant Inbred Lines Contrasting in Their P‐Efficiency

Abstract: Legumes' sensitivity to salt is exacerbated under growth conditions requiring nitrogen fixation by the plant. Phosphorus (P) deficiency is widespread in legumes, especially common bean (Phaseolus vulgaris L). To examine the performance of P. vulgaris under salt stress conditions, a field experiment was conducted using two recombinants inbred lines (RILs) 115 (P‐deficiency tolerant) and 147 (P‐deficiency susceptible), grown under different salinity levels (L) (1.56, 4.78, and 8.83 dS m−1 as LI, L2, and L3, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 36 publications
7
98
0
Order By: Relevance
“…Generally, vacuoles are a storage for P in leaves; nevertheless, P mobility is reduced in high salt existence (Bargaz et al, 2016). Indeed, one possible explanation for the increase of P concentration is that NaCl at low or moderate levels stimulates the P uptake of the bean.…”
Section: Phosphorus Concentration Of Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, vacuoles are a storage for P in leaves; nevertheless, P mobility is reduced in high salt existence (Bargaz et al, 2016). Indeed, one possible explanation for the increase of P concentration is that NaCl at low or moderate levels stimulates the P uptake of the bean.…”
Section: Phosphorus Concentration Of Plantmentioning
confidence: 99%
“…The availability of P in soil depends on soil properties such as pH, lime, texture, main material, salinity, etc. Salinity and P deficiency together affect negatively plant growth and crop productions in arid and semi-arid areas with calcareous soils (Bargaz et al, 2016 Phosphorus deficiency is perhaps the most limiting factor for symbiotic N-fixation, resulting from an association with rhizobial bacteria and leading to decrease in productivity of legume crops (Kouas et al, 2005). The common bean (Phaseolus vulgaris L.) is widely grown around the world and it is one of the most important nutritious crops as both green and dry, for direct human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Pulses are also a fairly good source vitamins (Aykroyd & Doughty, 1973;Gopalon et al, 1977 andGupta , 1982 ). Cultivation of legume is beneficial to other crops through multiple agro-ecological services increased soil fertility by biological nitrogen fixation and Increase soil content of nitrogen (Nasser et al, 2016;Bargaz et al, 2016 andKumar et al, 2014) .Faba bean (Vicia faba L.) is a main legume and seed is consumed by humans all over the world. Some varieties are remarkable livestock feed and used for fodder, hay, straw and silage (Prolea, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate (Pi) is the main form of phosphorus that plant can absorb from soil, and thus is the most limiting factor for plant production in many regions all over the world since the content of available Pi in soil is commonly insufficient (Hinsinger, 2001; Vance et al, 2003; Gaxiola et al, 2011; MacDonald et al, 2011; Bargaz et al, 2016). Therefore, the development of crops with improved phosphorus nutrition will contribute to improvement of crop productivity and reduction of phosphorus fertilizer application (Gaxiola et al, 2011, 2012; Yang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to salt and drought stress, inorganic phosphate (Pi) deficiency in soil is another limiting factor that affects the yield and persistence of alfalfa (Berg et al, 2009). Previous studies showed that soil Pi deficiency are common in areas (including northern China) growing alfalfa and other legume crops (Wang et al, 1998; MacDonald et al, 2011; Ma et al, 2012; Bargaz et al, 2016). In the past decades, farmers have to counter this problem through the application of phosphate fertilizer (Kochian et al, 2004; Gaxiola et al, 2011, 2012); however, this process resulted in the increase of cost and damage of environment (Giaveno et al, 2010; Gaxiola et al, 2011, 2012; Pei et al, 2012; Yang et al, 2014; Lv et al, 2015).…”
Section: Introductionmentioning
confidence: 99%